Penerapan Prinsip Equality Before the Law: Studi Pada Keterwakilan Perempuan dalam Politik: The Application of the Principle of Equality Before the Law: A Study on Women’s Representation in Politics - Yesa Amanda; Soraya Oktarina; Hendri Hendri (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2025)
The principle of equality before the law is one of the main pillars in the state of law. However, its implementation is often not fully felt by all parties, especially women in the political realm. This article discusses how legal equality for women is applied in the political world, the challenges faced, and steps that can be taken to address gender-based discrimination. The case study focuses on women's representation in the Indonesian parliament and the systemic barriers affecting their participation. This analysis was carried out using normative and empirical approaches, and supported by secondary data. The results of the study show that cultural, social, and policy constraints are still the main obstacles in achieving gender equality in politics.